Impact of suspended sediment on Pahang River development using Geographic Information System - Mustaffa, Hasmida; Kamarudin, Mohd Khairul Amri; Toriman, Mohd Ekhwan; Rosli, Mohd Hafz; Sunardi, Sunardi (Malaysian Institute of Planners, 2023)
The measurement of different characteristics of a stream, including integrated water resource management, is dependent on sediment transport mechanisms. On the Pahang River, studies explored the spatial interpolation pattern of suspended sediment (SS) and water resource management. Sedimentation issues in the Pahang River have a significant impact on water resource management in the Pahang River basin. Furthermore, it may have an impact on local water consumption, recreational activities, and other factors, causing the river to become shallow and finally flood. This study was conducted to determine the SS pattern in the Pahang River with the approach of the Geographic Information System (GIS) technique and its significant colour based on spatial analysis. In addition, this study also evaluates the factors and effects of sedimentation through water source management. Three sampling stations from the Department of Irrigation and Drainage (DID) for three years (2000, 2004 and 2008) were selected along thePahang River, where the parameter measured was suspended sediment (ton/year). The results obtained showed that the Pahang River receives a high amount of SS each year, where the higher amount was at the upper station (Sg. Yap), with an amount of 1876575 ton/year (2000), 613850.1 ton/year (2004) and 3458097 ton/year where it may be affected by sediment re-suspension and runoff from two outlets. Meanwhile, the downstream station (Lubuk Paku) received the least amount of SS, while the midstream station (Temerloh) received the most. The transit's speed and current may have an impact. This study's findings are critical in river and water resource management, especially of water resources for domestic use, ecotourism, river biodiversity, and hydrology.